2010
DOI: 10.4217/opr.2010.32.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Green Macroalgae (Ulva prolifera) Blooms in the Northern East China Sea in Summer 2008

Abstract: : This study examined extensive patches of floating green macroalgal (Ulva prolifera) mats in the northern East China Sea (ECS) using satellite images from mid May through July 2008 and field observation made during early August 2008 cruise. It was previously reported that the massive macroalgal blooms occurred in the coastal areas of Qingdao in China. During our field survey, researchers noticed widely distributed floating patches of macroalgal mats ranging in size from tens of centimeters to a few hundred me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Zhang et al (2011) reported that the blooming species forming the floating mats in the YS in 2008 and 2009 was U. prolifera based on a 5S rDNA spacer sequence analysis. (Choi et al 2010). The same phenomenon occurred in the southwest sea of Korea (the southeastern part of the YS) in 2009, and the green mats were senescent with reduced physiological activity (Kim et al 2011).…”
Section: Methodsmentioning
confidence: 87%
“…Zhang et al (2011) reported that the blooming species forming the floating mats in the YS in 2008 and 2009 was U. prolifera based on a 5S rDNA spacer sequence analysis. (Choi et al 2010). The same phenomenon occurred in the southwest sea of Korea (the southeastern part of the YS) in 2009, and the green mats were senescent with reduced physiological activity (Kim et al 2011).…”
Section: Methodsmentioning
confidence: 87%
“…However, in the next year a huge amount of the MAB (Ulva prolifera) suddenly deposited close to the Olympic Sports Center in Qingdao coastal areas of the YS, China, and thus received mass public attention [5]. Afterwards, it became a common phenomenon during mid−May and until July in that region [6][7][8]. Moreover, a huge amount of seaweed (brown seaweed Sargassum) mats piled up along the southwest islands of the Korean Peninsula and Jeju Island's coasts in the northern part of the East China Sea (ECS) [9].…”
Section: Introductionmentioning
confidence: 99%